Biogeochemical Niche of Magnetotactic Cocci Capable of Sequestering Large Polyphosphate Inclusions in the Anoxic Layer of the Lake Pavin Water Column - Bidaud, Cécile C.; Monteil, Caroline L.; Menguy, Nicolas; Busigny, Vincent; Jézéquel, Didier; Viollier, Éric; Travert, Cynthia; Skouri-Panet, Fériel; Benzerara, Karim; Lefevre, Christopher T.; Duprat, Élodie (Frontiers in Microbiology, 2022)
Magnetotactic bacteria (MTB) are microorganisms thriving mostly at oxic-anoxic boundaries of aquatic habitats. MTB are efficient in biomineralising or sequestrating diverse elements intracellularly, which makes them potentially important actors in biogeochemical cycles. Lake Pavin is a unique aqueous system populated by a wide diversity of MTB with two communities harbouring the capability to sequester not only iron under the form of magnetosomes, but also phosphorus and magnesium under the form of polyphosphates, or calcium carbonates, respectively. MTB thrive in the water column of Lake Pavin over a few meters along strong redox and chemical gradients representing a series of different micro-environments. In this study, we investigate the relative abundance and the vertical stratification of the diverse populations of MTB in relation with environmental parameters, by using a new method coupling a precise sampling for geochemical analyses, MTB morphotype description and in situ measurement of the physicochemical parameters. We assess the ultrastructure of MTB as a function of depth using light and electron microscopy. We evidence the biogeochemical niche of magnetotactic cocci, capable to sequester large PolyP inclusions below the oxic-anoxic transition zone. Our results suggest a tight link between the S and P metabolisms of these bacteria and pave the way to better understand the implication of MTB for the P cycle in stratified environmental conditions.